2020
DOI: 10.1177/1934578x20923181
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Antifungal Activity of Selected South African Plant Species Used for the Treatment of Skin Infections

Abstract: Dermatophytosis is a fungal infection of the skin caused by a group of pathogenic fungi known as dermatophytes. Therefore, we investigated those medicinal plants that were being used by local people and traditional healers to treat skin infections in the Mopani District, Limpopo Province. A survey was conducted through the use of a semistructured program to gather information on the common names, plant parts used, methods of preparation, and administration of the medicine. Findings of the survey revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…For example, triterpenes extracted from Combretum imberbe and Acacia mellifera showed antibacterial activity ( Angeh et al, 2007 ; Mutai et al, 2009a ). The majority of the plant species in which the spider nests were located in, are known for their antibacterial, antifungal, and/or antiviral activity, even when detailed studies on the chemical compositions are lacking ( Masoko et al, 2007 , 2010 ; Peloewetse et al, 2008 ; Mutai et al, 2009b ; Arbab et al, 2015 ; Lamola et al, 2017 ; Shikwambana and Mahlo, 2020 ). All in all, we found several VOCs in the nest, web, and spider volatilomes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, triterpenes extracted from Combretum imberbe and Acacia mellifera showed antibacterial activity ( Angeh et al, 2007 ; Mutai et al, 2009a ). The majority of the plant species in which the spider nests were located in, are known for their antibacterial, antifungal, and/or antiviral activity, even when detailed studies on the chemical compositions are lacking ( Masoko et al, 2007 , 2010 ; Peloewetse et al, 2008 ; Mutai et al, 2009b ; Arbab et al, 2015 ; Lamola et al, 2017 ; Shikwambana and Mahlo, 2020 ). All in all, we found several VOCs in the nest, web, and spider volatilomes.…”
Section: Discussionmentioning
confidence: 99%
“…Its antifungal activity was comparable to that of the ethyl acetate (ZOI = 20 mm) and methanolic (ZOI = 25 mm) extracts against the six tested fungal strains: Absidia corymbifera, Aspergillus fumigatus, Candida krusei, Microsporum gypseum, Mucor species and Trichophyton mentagrophytes with ZOI ranging between 15 mm and 20 mm (34). Acetonic and aqueous extracts of E. divinorum roots were indicated to excert antifungal activity against C. albicans, Microsporum canis and Trichophyton rubrum with average MIC of 0.23 to 0.47 mg/mL (79). Kilonzo et al (25) reported that petroleum ether, ethyl acetate and aqueous extracts of E. divinorum leaves, stem bark and root bark showed antimicorbial activity against S. aureus (MIC = 0.718 to >25 mg/mL), Klebsiella pneumoniae (MIC = 0.718 >25 mg/mL), E. coli (MIC = 0.718 >25 mg/mL), Salmonella typhi (MIC = 0.718 to >25 mg/mL), C. albicans (MIC = 0.718 to >25 mg/mL), and C. neoformans (MIC = 0.718 to >25 mg/mL).…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…are symbolically revered as Haaganaa trees (trees ordained by mystical powers) and are used in rituals of avoiding inauspicious omen, idiotism, homicide case resolution and mythical power expression (72). In South Africa, E. divinorum is used in magical practices (79). (106).…”
Section: Ethnomedicinal Uses Of E Divinorummentioning
confidence: 99%
“…Several studies have reported the potential antifungal activity of the root and root bark of most Diospyros species [42,54,92]. However, the antifungal activity of a leaf extract of D. mespiliformis has also been confirmed [47,93].…”
Section: Antifungal Activitymentioning
confidence: 99%